Combined HPV and CINtec PLUS testing for triaging cervical cancer screening in a Belgian cohort - Louise Cras; Stefanie Brock; Kurt Barbé; Hanne Locy; Glenn Broeckx; Shaira Sahebali (Annals of Cytology and Pathology - Peertechz Publications, 2023)
Background: Cytological screening with Human Papillomavirus (HPV) triage for equivocal results has been the routine screening procedure for cervical cancer for years worldwide. The dual-marker stain p16/Ki67 (CINtec PLUS) has been shown to offer high sensitivity and specificity in the triage of women at risk of developing HPV-related precancerous lesions. We evaluated the utility of CINtec PLUS in women with normal cytology and a positive HPV test, to see if this test can be used as a prognostic biomarker.   Methods: Women of 18 years or older were assembled between January 2018 and December 2022 at two different study sites. These were cytology negative for intra-epithelial Neoplasia (NILM) and a positive HPV test. The prognostic value of the CINtec PLUS test for NILM samples and the confounding effect of HPV subtype, age, university, and follow-up stage were evaluated.   Results: CINtec PLUS was positive in 63 out of 312 (20%) NILM/ HPV-positive cases. The Positive Predictive Value (PPV) of CINtec PLUS was 92% for high-grade dysplastic lesion (HSIL), 64% for NILM, and 31% for low-grade dysplasia. The negative predictive value was 83% for HSIL, 64% for NILM, and 83% for low-grade dysplasia.   Conclusion: Adding CINtec PLUS with NILM cytology and HPV-positive test can be an important prognostic tool to identify women at risk for a high-grade dysplastic cervical lesion. Importantly, the test can also be used in primary HPV screening programs. However, women with low-grade dysplasia remain at risk for over- and under-treatment.